Management of a loan portfolio of a commercial bank (Journal of Economic Research & Business Administration, 2016)
A service of crediting is one of the most profitable items of a commercial bank. It is the crediting that forms a basic part of the net profit, which further is listed into the reserve funds. Simultaneously credits’ defaults (especially of the large credits) promoted bank’s bankrupt and later, due to bank’s importance on the macroeconomical level, it causes bankrupts of companies, legal entities and individuals.Bank activity is directly connected to different risks in the process of bank’s communications with clients and other banks. Loan risk is the main threat for succesful bank functioning. Increasing the volume of problem loans in the structure of a loan portfolio makes a negative influence on a reputation and a position of a bakn in the market of credit resourses. The issues of management of a loan portfolio of a commercial bank is considered in this article.
Keywords: Commercial banks; problem loans; provisions; market; past due debt; The National Bank.